Nghiên cứu các nhân tố tác động đến việc sử dụng hệ thống SCM tích hợp Blockchain trên sàn thương mại điện tử - Nguyễn Thị , Hội; Trần Thị, Nhung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
In the rapidly developing environment of international trade, supply chain management systems have developed into a large ecosystem and blockchain technology has strongly impacted the operations of these supply chain systems. With the goal of studying the intention to use blockchain technology in supply chain management systems, especially in e-commerce, the research used SEM and UTAUT2 models along with data collection from 148 sellers and 248 consumers on Shopee.vn for implementation. The research results shows that performance expectations, effort expectations, favorable conditions, behavioral intentions have a proportional impact on the intention to use blockchain technology in supply chain management. That means that the trend of applying and integrating new technologies into application systems is being very well received not only in the world but also in Vietnam.